Early versus late enteral nutrition in critically ill patients receiving vasopressor support. Issue 1 (21st October 2021) - Dorken Gallastegi, Ander; Gebran, Anthony; Gaitanidis, Apostolos; Naar, Leon; Hwabejire, John O.; Parks, Jonathan; Lee, Jarone; Kaafarani, Haytham M. A.; Velmahos, George C.; Mendoza, April E.
Abstract: Background: Outcomes of early enteral nutrition (EEN) in critically ill patients on vasoactive medications remain unclear. We aimed to compare in‐hospital outcomes for EEN vs late EN (LEN) in mechanically ventilated patients receiving vasopressor support. Methods: This was a retrospective study using the national eICU Collaborative Research Database. Adult patients requiring vasopressor support and mechanical ventilation within 24 h of admission and for ≥2 days were included. Patients with an admission diagnosis that could constitute a contraindication for EEN (eg, gastrointestinal [GI] perforation, GI surgery) and patients with an intensive care unit (ICU) length of stay (LOS) <72 h were excluded. EEN and LEN were defined as tube feeding within 48 h and between 48 h and 1 week (nothing by mouth during the first 48 h) of admission, respectively. Propensity score matching was performed to derive two cohorts receiving EEN and LEN that were comparable for baseline patient characteristics. Results: Among 1701 patients who met the inclusion criteria (EEN: 1001, LEN: 700), 1148 were included in propensity score–matched cohorts (EEN: 574, LEN: 574). Median time to EN was 29 vs 79 h from admission in the EEN and LEN groups, respectively. There was no significant difference in mortality or hospital LOS between the two nutrition strategies. EEN was associated with shorter ICU LOS, lower need for renal replacement therapy, and lower incidence of electrolyte abnormalities. Conclusion: This study showed no difference in 28‐day mortality between EEN and LEN in critically ill patients receiving vasopressor support.